Pelatihan Kreatifitas dalam Membuat Produk Bernilai dari Kain Perca untuk Menggerakkan Ekonomi Masyarakat - Rabihat, Hannana; Karimah, Hamdatul; Muhaimin, Hamid; Akbar, Ilham; Sihite, Mislan (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This training aims to develop creativity in creating valuable products from patchwork to stimulate the community's economy. The method used is ABCD (asset-based community development), which focuses on utilizing local assets to build community capacity. The results of the service show that woven fabric is a typical fabric of the city of Kediri, with types such as sarong gombyor, misris cloth, semi-silk, and silk. The process of making woven cloth involves the use of fine threads and goes through two stages of work with 14 stages. The large number of rags or fabrics left over from production is the potential that is utilized in this training. The patchwork is processed into various accessories, such as brooches and key chains, that can be used by all groups. It is hoped that the use of patchwork as an accessory will attract the attention of various levels of society because of its affordable price. This allows people who are constrained by high prices to still collect woven fabric-based products at lower prices, thereby contributing to improving the local economy.